2003
DOI: 10.1089/105072503322240004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Thyroidectomy Alone or Followed by Radioiodine Ablation of Thyroid Remnants on the Outcome of Graves' Ophthalmopathy

Abstract: Fifty-five patients with Graves' disease (GD) and mild to moderate Graves' ophthalmopathy (GO) underwent near-total thyroidectomy (Tx). In 16 patients this was followed by a standard ablative dose of (131)I because of the hystologic evidence of differentiated thyroid carcinoma. We retrospectively evaluated whether or not GO activity could be affected by thyroid surgery alone or followed by complete ablation of thyroid tissue. Accordingly, on the basis of clinical activity score (CAS) values prior to thyroidect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 25 publications
1
18
0
2
Order By: Relevance
“…Finally, RAI can also be administered after surgery to attain total ablation of thyroid tissue, which might be beneficial for its complete removing of thyroid antigen(s) and autoreactive T lymphocytes likely involved in the pathogenesis of GO (1). Indeed, few studies have suggested that total thyroid ablation is more frequently associated with GO improvement than surgery alone (46,47,48,49,50). According to the recently published Italian guidelines on the treatment of hyperthyroidism in patients affected with GD and GO (51), total thyroid ablation may be suggested when trying to achieve earlier inactivation of GO that can be followed, when needed, by prompt rehabilitative surgery.…”
Section: Current Guidelines For Treatment Of Thyroid Dysfunction In Pmentioning
confidence: 99%
“…Finally, RAI can also be administered after surgery to attain total ablation of thyroid tissue, which might be beneficial for its complete removing of thyroid antigen(s) and autoreactive T lymphocytes likely involved in the pathogenesis of GO (1). Indeed, few studies have suggested that total thyroid ablation is more frequently associated with GO improvement than surgery alone (46,47,48,49,50). According to the recently published Italian guidelines on the treatment of hyperthyroidism in patients affected with GD and GO (51), total thyroid ablation may be suggested when trying to achieve earlier inactivation of GO that can be followed, when needed, by prompt rehabilitative surgery.…”
Section: Current Guidelines For Treatment Of Thyroid Dysfunction In Pmentioning
confidence: 99%
“…On the other hand, ATD treatment is associated with a high relapse rate after drug withdrawal [19], and the continuing thyroid hyperactivity and fluctuations in thyroid hormone and TSH serum levels, during or after ATD treatment might negatively influence the course of GO. Thus, after control of hyperthyroidism with ATD, the thyroid could be surgically ablated while GO is concomitantly managed with pulse corticosteroids [20,21,22,23,24]. Currently, evidence is scant for the superiority of the conservative approach over the surgical approach or vice versa [25].…”
Section: Discussionmentioning
confidence: 99%
“…Total thyroid ablation (radioiodine ablation after thyroidectomy) has been proposed as a means of inducing and maintaining GO inactivity, though this therapeutic strategy for GO remains controversial [15,16,17]. In our 3 cases, radioiodine treatment was given 3 days after the rhTSH at the peak of the TSH (>80 mU/l) without prophylactic steroid treatment.…”
Section: Discussionmentioning
confidence: 99%